2022
DOI: 10.5130/cjlg.vi26.8189
|View full text |Cite
|
Sign up to set email alerts
|

Visualising the invisible: collaborative approaches to local-level resilient development in the Pacific Islands region

Abstract: The Pacific Islands region has made strong progress on the integration of climate change, disaster management and development frameworks, particularly via the Pacific Urban Agenda and the Framework for Resilient Development in the Pacific. These frameworks highlight the need for local- level collaboration in achieving ambitious pathways for climate- and disaster-resilient development. However, to date little research has investigated the role that local-level collaboration plays in implementation. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Yet, an audit of the Australian government documentation conducted for this research revealed there is little acknowledgement of the worldviews of the citizens or communities in the aid-receiving countries or their connections to the natural environment and, most importantly, how this influences stakeholder uptake of foreign-funded interventions [16,17]. For, if the success of climate change projects is tied to an understanding of the interconnectedness between the people, their spirituality, the land, and the environment, then it follows that the effectiveness and sustainability of aid projects hinge on their adoption of holistic perspectives [18,19]. There is thus a tension between secular funders, who generally do not acknowledge the spirituality of the recipients, and the values and practices of the recipient populations that hold spiritually informed worldviews, especially in the Pacific [2,11].…”
Section: Social Context Study Framework and Intended Contributionmentioning
confidence: 99%
“…Yet, an audit of the Australian government documentation conducted for this research revealed there is little acknowledgement of the worldviews of the citizens or communities in the aid-receiving countries or their connections to the natural environment and, most importantly, how this influences stakeholder uptake of foreign-funded interventions [16,17]. For, if the success of climate change projects is tied to an understanding of the interconnectedness between the people, their spirituality, the land, and the environment, then it follows that the effectiveness and sustainability of aid projects hinge on their adoption of holistic perspectives [18,19]. There is thus a tension between secular funders, who generally do not acknowledge the spirituality of the recipients, and the values and practices of the recipient populations that hold spiritually informed worldviews, especially in the Pacific [2,11].…”
Section: Social Context Study Framework and Intended Contributionmentioning
confidence: 99%